BUSINESS ECOSYSTEM IN EDUCATION FINANCING INDEPENDENCE BASED ON BOARDING SCHOOL (CASE STUDY OF RAUDHATUL MUBTADIIN BOARDING SCHOOL, BALEKAMBANG, JEPARA) - Choir, Abu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the business ecosystem that supports independent education financing at the Raudhatul Mubtadiin Balekambang Islamic Boarding School, Jepara. The research method used is a case study with a qualitative approach, through in-depth interviews and participant observation. Education at Islamic boarding schools has a significant role in developing religious, moral and academic values among students. However, the continuity of education in Islamic boarding schools often depends on financial independence. The research results show that the business ecosystem in Islamic boarding schools consists of various components, including the active role of local communities, collaboration with the private sector, as well as internal initiatives in Islamic boarding schools in managing resources effectively. Education financing is supported by contributions from donors, waqf funds, as well as management of productive assets such as agriculture and creative industries. Apart from that, the partnership model with microfinance institutions also helps strengthen the economy of Islamic boarding schools